1983
DOI: 10.1177/028418518302400410
|View full text |Cite
|
Sign up to set email alerts
|

Intrarenal Backflow and Renal Perfusion during Increased Intrapelvic Pressure in Excised Porcine Kidneys

Abstract: The effect of increased intrapelvic pressure on renal perfusion was examined by simple magnified angiography of freshly excised artificially perfused kidneys of adult Danish Landrace pigs. In all kidneys control angiography was performed at normal intrapelvic pressure (0-5 mmHg). Intrapelvic pressure was raised by retrograde ureteral perfusion of saline in 9 kidneys. Repeat angiography was performed at an intrapelvic pressure of 30-35 mmHg (4 kidneys), 50-55 mmHg (5 kidneys) or 0-5 mmHg (4 kidneys). Angiograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

1983
1983
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…According to the Jung's et al study, with the use of forced irrigation during ureteroscopy, intrarenal pressure increases above 300 mmHg 14 . And it was established that according to the results obtained from some animal and human studies, when intrarenal pressure rises above 30 mmHg, some defence mechanisms which depend on the intrarenal pressure including pyelo‐tubular, pyelo‐venous, pyelo‐sineous and pyelo‐lymphatic backflow come into play 15‐18 . These mechanisms have the potential to decrease kidney function as well as they may be related to infectious and hemorrhagic process 14 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the Jung's et al study, with the use of forced irrigation during ureteroscopy, intrarenal pressure increases above 300 mmHg 14 . And it was established that according to the results obtained from some animal and human studies, when intrarenal pressure rises above 30 mmHg, some defence mechanisms which depend on the intrarenal pressure including pyelo‐tubular, pyelo‐venous, pyelo‐sineous and pyelo‐lymphatic backflow come into play 15‐18 . These mechanisms have the potential to decrease kidney function as well as they may be related to infectious and hemorrhagic process 14 .…”
Section: Discussionmentioning
confidence: 99%
“…But, we associated this difference with the length of the OT in the group which used the UAS. While some studies in the literature focused on some of the benefits of the sheath, they indicated its importance in terms of infection formation, indirectly interpreting the results they obtained from these studies 4,9,10,15‐17,19 …”
Section: Discussionmentioning
confidence: 99%
“…According to the Jung's et al study, with the use of forced irrigation during ureteroscopy, intrarenal pressure increases above 300 mmHg 13 . And it was established that according to the results obtained from some animal and human studies, when intrarenal pressure rises above 30 mmHg, some defense mechanisms which depend on the intrarenal pressure including pyelo-tubular, pyelo-venous, pyelo-sineous and pyelo-lymphatic backflow come into play [14][15][16][17] . These mechanisms have the potential to decrease kidney function as well as they may be related to infectious and hemorrhagic process 13 .…”
Section: Discussionmentioning
confidence: 99%
“…As it is known from animal and human studies, with an increase of intrarenal pressure to 20-30 mmHg, pyelo-tubular backflow develops and blood circulation of the kidney decreases (13,14). When intrarenal pressure increases to 30-50 mmHg, the pyelovenous backflow becomes more evident and an increase in both pyelosinus and pyelolymphatic pressures results in forniceal rupture (14,15).…”
Section: Discussionmentioning
confidence: 99%